The Psychological reader's guide.
Monthly. Tables of contents of current psychology journals. Worldwide coverage. Alphabetical arrangement by journal titles. Each issue has list of journals covered that month. Occasional listings of all journals currently covered. As of Feb. 2, 1976, primary authors' addresses included.